The Professional Profile of a Post-editor according to LSCs and Linguists: a Survey-Based Research - Ginovart Cid, Clara (HERMES - Journal of Language and Communication in Business, 2020)
The boundaries between translation technologies are fading and language professionals are heading towards a pluri- and transdisciplinary job description, for which the use of CAT tools, translation management systems, and machine translation (MT) are compulsory. “Language paraprofessionals”, “paralinguists”, “language consultants”, “digital linguists”, and a long list of other titles is emerging to refer to the professionals who master a number of features of several tools, while remaining attentive to linguistics (see Bond 2018). According to TAUS DQF Dashboard data presented in TAUS Newsletter the 1st of May of 2019, the industry averages show that 9.7% of the translation output origin comes from MT and that 1,057 words per hour are post-edited on average. This has clear repercussions on the profession from the employability perspective.With 66 submissions by LSCs and industry stakeholders, and 142 answers from individuals (in-house or freelance translators), we present the most salient subject matters from and for the translation industry regarding MT post-editing. Some represent gaps to be filled; others represent common ground already found. Thanks to this up-to-date knowledge of the globalization landscape, clear goals can be set, and the way is paved for evolution.